COOLING OF BAR AND STABILIZING OF THERMAL MODE IN CRYSTALLIZER OF CASTING - RENTAL AGGREGATE - Nikolaenko , Anatoly; Yakushevich , Ivan (Scientific Journal "Metallurgy", 2020)
The performance of the casting unit depends largely on the operation of the ingot cooling system, whose main purpose is the continuous and gradual removal of heat during the conversion of molten aluminum to a solid workpiece. However, in the technical documentation for continuous casting and aluminum rolling lines, manufacturers do not provide specific information on the adjustment of cooling systems, which significantly complicates the start-up of rolling-stock units. In this regard, there is a need to develop recommendations for determining the total flow rate of water for cooling the ingot, as well as the algorithm for distributing it between the individual zones of the mold and creating conditions for stabilization of its thermal regime. Based on the analysis of the equilibrium balance of the crystallizer of the continuous casting machine of aluminum and the mathematical ratios for calculating its components, it is established that the value of the total heat lost with the cooling water can calculate the required total water flow to cool the ingot in the foundry machine. An algorithm for the distribution of the determined water flow between the individual zones of the crystallizer is proposed taking into account the coefficients of heat transfer of its multilayer wall in these zones and the system of automatic control, which by the amount of heat discharged from the crystallizer with the solidified workpiece and the value of heat loss by the cooling water the crystallizer is not only in deviation but also in perturbation. The study of the proposed system was performed on a computer model, created with the help of programming packages of microprocessor controllers "UnityPro" manufactured by "Schnider Eleсtric" and "TIA Rortal" of "Siemens", showed high quality of its work and stability in the appearance of both external and internal disturbances.